Harmonized System: Nomenclature Evolution at Its 20th Anniversary (1988–2008) - Carsten Weerth (Global Trade and Customs Journal, 2008)
More than 200 countries and economic regions worldwide are using the nomenclature of the Harmonized Commodity Description and Coding System (Harmonized System Convention, HS) and are basing their customs tariffs thereon. The number of HS headings (four-digit-code) and HS-subheadings (six-digit-code) is altered every four to six years, when the nomenclature is revised and updated due to trade patterns and technical development (HS 1988, HS 1992, HS 1996, HS 2002, HS 2007). More and more gaps are emerging within the nomenclature 34 headings are not in use in the HS 2007 for the next four to five years. This Column shows the history of HS revisions, the gaps within the nomenclature and the evolution of the HS nomenclature within the past 20 years (1988-2008).
Additional information: Archiving of proofs, accroding to ROMEO-Entry.
Keywords: F53; K33; K34; 330; Customs Law; Customs Classification; Tariff Classification; Harmonized System; World Customs Organization; Trade Law